Factors Affecting Inpatient Satisfaction At General Hospital Of Hasanuddin Damrah Manna In South Bengkulu Regency - Nisah, Cintia Chairu; Irwanto, Tito; Astuty , Kamelia (Journal of Accounting and Management, 2025)
Quality of service is the degree of providing efficient and effective services in accordance with professional standards, service standards that are implemented comprehensively according to patient needs, utilizing appropriate technology and research results in developing health services so that optimal health levels are achieved. This study aims is to have a very strategic role in accelerating the improvement of public health in providing health services. This research method uses a quantitative research method with a cross-sectional approach. The population in this study were all patients who came for inpatient care at the General Hospital of Hasanuddin Damrah Manna in South Bengkulu Regency, totaling 3,169 patients. The sample to be studied was 97 respondents. The sampling technique in this study used the Purposive Sampling technique. Data were analyzed by conducting a chi-square analysis test. The conclusion of this study is that all independent variables have an influence on the quality of health services at the General Hospital of Hasanuddin Damrah Manna in South Bengkulu Regency, (Tangible p=0.013, Reliability p=0.012, Responsiveness p=0.006, Assurance p=0.016 and Empathy p=0.012) and the most dominant variable is the Responsiveness variable p=0.006.